2005
DOI: 10.1063/1.2034327
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of turbulence at low power input in a model for plasma confinement transitions

Abstract: A physics-based condition is used to unfold a trapped or persistent degenerate singularity in a dynamical model for plasma confinement transitions. The bifurcation structure of the resulting enhanced model indicates that shear flow can actually grow as the power input is withdrawn, with concomitant supersuppression of turbulence. This is an important and testable prediction that suggests new design, management, and optimization strategies for new-generation fusion experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…However, the tradeoff with such highly coarsegrained modeling is that it necessarily whites out information, and may therefore miss important physics and predict unphysical singular behavior [15]. Thus we require validation of the low-dimensional modeling results by computational simulations of finer models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tradeoff with such highly coarsegrained modeling is that it necessarily whites out information, and may therefore miss important physics and predict unphysical singular behavior [15]. Thus we require validation of the low-dimensional modeling results by computational simulations of finer models.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest approach that captures the essential physics underlying the problem is lowdimensional dynamical modeling and analysis [13,14,15,16], which can provide a very economical tool to predict the transition. However, the tradeoff with such highly coarsegrained modeling is that it necessarily whites out information, and may therefore miss important physics and predict unphysical singular behavior [15].…”
Section: Introductionmentioning
confidence: 99%
“…The creation of an edge transport barrier formed by a sheared zonal flow is closely related to the L-H transition 3 . Ordinary differential equation (ODE) models for the L-H transition are based on the predator-prey relationship between zonal flow and turbulent flow, and incorporate a potential energy related to the pressure profile as an additional state variable [4][5][6][7][8][9][10][11][12] . Miki et al 13 and Wu et al 14 have both suggested 1D partial differential equation (PDE) models for the L-H transition based on this predator-prey relationship.…”
Section: Introductionmentioning
confidence: 99%